ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA STATISTIKA SMA DAN BENTUK SCAFFOLDING YANG DIBERIKAN - Chamid Al-chalimy, Abdul; Rinda Prihartiwi, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Statistics word problems require students to understand the context of the problem, translate the information into a mathematical model, and solve it using statistical concepts. However, students are still found to make errors in the problem-solving process. This study aims to describe the types of errors students make when solving statistical word problems based on Newman’s analysis, the types of scaffolding provided, and the types of errors that still occur after scaffolding is provided. This study employs a qualitative approach and a descriptive research design, with three 10th-grade high school students selected as subjects based on the results of a pre-test, using the criterion of having the greatest variety of error types. Data were collected through statistical word problem tests and interviews using test instruments and interview guidelines. Data analysis included data reduction, data presentation, and drawing conclusions, while error identification referred to Newman’s analysis indicators. The results showed that students made five types of Newman errors: reading errors, comprehension errors, transformation errors, process skill errors, and errors in writing the final answer. The scaffolding provided included reviewing, explaining, and restructuring, tailored to the types of errors made by the students. After scaffolding was provided, some recurring errors were still found, although improvements were observed in the problem-solving process. Thus, scaffolding helps improve the process of solving statistical word problems but has not completely eliminated errors; therefore, continuous practice and reinforcement are necessary. Future research is recommended to develop test instruments with a consistent data presentation format, consider the timing of data collection so as not to disrupt students’ concentration, and provide students with the opportunity to restate their solutions and conclusions in their own words after receiving scaffolding to assess the level of understanding they have achieved